Outstanding platinum group metal-free bifunctional catalysts for rechargeable zinc-air batteries. (1st April 2023) - Muuli, Kaur; Lyu, Xiang; Mooste, Marek; Käärik, Maike; Zulevi, Barr; Leis, Jaan; Yu, Haoran; Cullen, David A.; Serov, Alexey; Tammeveski, Kaido
Abstract: Developing highly active and durable catalysts for zinc-air batteries (ZAB) is critical for energy conversion and storage. Herein, we prepared Fe-N-C catalysts at a kilogram scale by the commercial VariPore™ method and the effect of synthesis conditions on the catalyst performance at ZAB air electrode was investigated. The results show the PA-450-HT exhibits excellent electrocatalytic activity toward oxygen reduction reaction (ORR) and it is the most suitable catalyst for primary ZAB with the galvanostatic polarization discharge peak power density of 149 mW cm −2, outperforming commercial Pt-Ru/C catalysts. Additionally, the NCB-600-HT catalyst displays the half-wave potential of 0.87 V vs. RHE for ORR and ∆ E value of 0.81 V (indicating outstanding ORR and OER reversibility) and exhibits excellent charge-discharge cycling durability similar to NCB-550-LT around 160 h for the secondary ZAB. This work reports outstanding bifunctional Fe-N-C catalysts for rechargeable ZAB at mass production for the first time. Graphical abstract: Image, graphical abstract